Pejuang Muda Manifetasi Gerakan Pengabdian Oleh Mahasiswa : Dalam Pengembangan Potensi Desa Ngreco - Wildan Wahid Hasyim (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The devotion of young fighters under the auspices of the Ministry of Social Affairs aims to build villages so that the village's potential can be enjoyed by villagers. The problem that arises is the lack of a moratorium and supervision by the government and related agencies. With this program, problems with the agency can be resolved through FGD forums and collective program implementation. The selection of this dedication topic is based on the existence of tourism potential that is quite profitable for the residents of Ngreco Village. The service method is carried out in several stages, namely planning, program implementation and program evaluation on a regular basis. From this service, it produces many benefits that are felt by the community, especially the local community, namely by creating job opportunities and the formation of a new economic circulation that breaks down the income of residents, not only that, the district government as a regional administrative leader also feels the benefits.